Access to justice for victims of economic exploitation - White, Robert McKay (My University, 2024)
Research in intimate partner violence (IPV) has established that economic abuse, including economic exploitation, is an important form of IPV that is often used to trap victims in an abusive relationship. Though victims of all types of IPV encounter particular barriers to accessing justice, there are particular issues for those victimized by economic exploitation. This article explains the prevalence and consequences of economic exploitation and explores the indicators that victims lack access to justice. It proposes the primary obstacles victims of economic exploitation encounter and urges specific actions to assist lawyers, judges, and legislators in recognizing economic exploitation in intimate partner relationships and promoting appropriate remedies. This is particularly important for women, which data analysis indicates are at greater risk for this type of abuse.
Keywords: intimate partner violence; economic exploitation; government policy; criminology